The financial and macroeconomic effects of OMT announcements - Carlo Altavilla; Domenico Giannone; Michele Lenza (European Central Bank (ECB), 2014)
This study evaluates the macroeconomic effects of Outright Monetary Transaction (OMT) announcements by the European Central Bank (ECB). Using high-frequency data, we find that OMT announcements decreased the Italian and Spanish 2-year government bond yields by about 2 percentage points, while leaving unchanged the bond yields of the same maturity in Germany and France. These results are used to calibrate a scenario in a multi-country model describing the macro-financial linkages in France, Germany, Italy, and Spain. The scenario analysis suggests that the reduction in bond yields due to OMT announcements is associated with a significant increase in real activity, credit, and prices in Italy and Spain with relatively muted spillovers in France and Germany.
Keywords: E47; E58; C54; 330; Event study; multi-country vector autoregressive model; news; Outright Monetary Transactions